Contemporary sport management - Thibault, Lucie PhD; Pedersen, Paul M. PhD 1970- (Champaign, IL Human Kinetics, Inc., 2022)
Short, factual description of the book (summary of what it includes, without subjective or promotional language.) This classic but thoroughly updated introductory text is designed so students will understand sport management as a field of study and a vibrant professional environment. It emphasizes critical-thinking, ethics, and diversity while providing a broad introduction to the major functional areas and issues that student will encounter in their careers
1. Managing sport -- 2. Developing a professional perspective -- 3. Management concepts and practice in sport organizations -- 4. Managing and leading in sport organizations -- 5. Sociological aspects of sport management -- 6. Sport management research -- 7. Managing sport participation across the life span -- 8. Interscholastic athletics -- 9. Intercollegiate athletics -- 10. Professional sport -- 11. Sport management and marketing agencies -- 12. International sport management -- 13. Emerging developments in sport management -- 14. Sport marketing -- 15. Sport sales and consumer behavior -- 16. Analytics in the sport industry -- 17. Communication in the sport industry -- 18. Finance and economics in the sport industry -- 19. Sport facility and event management -- 20. Legal considerations in sport management
Includes bibliographical references and index
Keywords: Sports administration; Physical education and training -- Administration